Ensino de relações nome-objeto e aprendizagem de relações emergentes por bebês - Souza, Leylanne Martins Ribeiro de (Universidade Federal de São Carlos, 2018)
The studies reported in this dissertation specifically addressed the population of toddlers, aged between 14 and 25 months age. The studies investigated the teaching of name-object relations in tasks of auditory-visual conditional discrimination, and the emergence and stability of new name-object relations in toddlers. Study 1 verified for seven children, aged between 18 and 22 months, the establishment of relations between words and objects using discrimination probes – which evaluated the sample-S+ relation – after the emergence of a conditional relation in responding by exclusion. Emergence of conditional relations was verified with exclusion probes and establishment of emergent relations was tested through discrimination probes. Six out of seven children responded by exclusion. One participant responded to the stimuli from the discrimination probes after ten trials: one exclusion trial and nine subsequent trials, similar to exclusion trials, and maintained consistent responses in the follow-up between two and six days. Study 2 carried out with 19 children between 14 and 25 months old, evaluated learning of name-object relations, after emergence of the conditional relation in responding by exclusion, through discrimination probes, and compared the performance of the participants in the discrimination probes with the performance on the learning and naming probes. Six out of 19 participants responded by exclusion. Discrimination probes attested learning of two nameobject relations by three participants. One participant’s responses were consistent with learning two relations after taught emergent name-object relations. In Study 3 we tried to identify the variables that could cause the errors occurred in the teaching of name-object conditional discriminations defined for the 19 children who participated in Study 2. All children had the repertoire evaluated by the Inventário Portage Operacionalizado (IPO) on four occasions: the first at the beginning of the data collection and the last one immediately before the closing of the research participation. For the analysis of the data, two types of procedure were performed: categorization of participants' performance in the different stimulus arrangements of matchingto-sample (MTS with one, two and three stimuli comparison); and comparison of the median of the IPO results of the group of children in relation to the overall score and in the areas of Cognition and Language. The analyzes suggest that there was a lack of prerequisite behaviors for the selection of the correct stimulus in the MTS tasks as an explanatory possibility for the occurrence of errors. The three studies provided evidence difficulties and potentialities of the procedures when destined to toddlers with the purpose of teaching and the maintenance of emergent relations by exclusion.
Teaching of name-object relations and learning of emerging relations by toddlers
Keywords: Responder por exclusão; Sondas de discriminação; Aprendizagem; Discriminação condicional; Bebês; Responding by exclusion; Discrimination probes; Learning; Conditional discrimination; Toddlers; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL